Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1017/s0025315400059452
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of a coastal Phaeocystis bloom in the north-western English Channel in 1990

Abstract: The evolution of a Phaeocystis bloom off Plymouth in spring 1990 is described. Data were obtained (1) during weekly visits to station El to measure physical parameters, nutrient concentrations, primary production and grazing pressure and (2) by regular tows of an Undulating Oceanographic Recorder around a circuit of five stations including El to detect stratification, monitor the geographical distribution of chlorophyll and determine vertical profiles at each station.The data show that the Phaeocystis bloom em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
(39 reference statements)
0
32
1
Order By: Relevance
“…It has been suggested (Veldhuis et al 1986, Lancelot & Mathot 1987 that Phaeocystis blooms follow a diatom bloom, which exhausts silicate but does not remove all nitrate and phosphate and these nutnents are then available to Phaeocystis. However, this succession does not always occur and Davies et al (1992) have described a Phaeocystis bloom which occurred in coastal waters without a major diatom bloom; similarly, in the North Sea in 1989, there was no evidence of a diatom bloom in the eastern North Sea at the time that samples were taken and the Phaeocystis bloom was not preceded by sillcate depletion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been suggested (Veldhuis et al 1986, Lancelot & Mathot 1987 that Phaeocystis blooms follow a diatom bloom, which exhausts silicate but does not remove all nitrate and phosphate and these nutnents are then available to Phaeocystis. However, this succession does not always occur and Davies et al (1992) have described a Phaeocystis bloom which occurred in coastal waters without a major diatom bloom; similarly, in the North Sea in 1989, there was no evidence of a diatom bloom in the eastern North Sea at the time that samples were taken and the Phaeocystis bloom was not preceded by sillcate depletion.…”
Section: Discussionmentioning
confidence: 98%
“…Davies et al (1992) have suggested that the initiation of a Phaeocystis bloom may occur when growth begins of cells which have persisted throughout the winter on the sediment. In these circumstances, light would be required to penetrate to the sea bed in the late winter for growth of Phaeocystis to be initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Although extrapolating laboratory results to the field can be challenging, patterns from field studies are consistent with our laboratory experiments. For example, blooms of Phaeocystis colonies frequently start during periods of low copepod abundance, and thus low grazing, when cues suppressing colony formation should also be low (30,31). In addition, the maximum concentration of Phaeocystis colonies reportedly occurs during, or near, maximum microzooplankton densities when colony-enhancing cues should be most abundant (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…cultures were fed Isochrysis galbana with f/2 vitamins and trace metals added and were grown at 25 E m Ϫ2 s Ϫ1 . Our experiments were set up with solitary cells or colonies as needed for the specific experiments, but it is common for field samples to vary from extremes of most cells occurring as solitary cells to most occurring within colonies and for these conditions to shift with time and location (31,42,43). Thus, all of our ratios of solitary cells to colonies may have real-world parallels in some locations or times.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the increase of nutrients in coastal waters is very likely responsible for the massive increase of PhaeocFstis, the algae responsible for the masses of foam that disfigure many North Sea beaches (Lancelot et al, 1987: Cad~e, 1990. Because species of zooplankton such as copepods, have feeding preferences for different species of phytoplankton (Davies et al, 1992), and because they in turn are important links in the marine food web, the change in Phaeocystis abundance could weU have important implications for coastal North Sea ecosystems in general and for fisheries in particular. Yet even a partial untangling of the effects on the food web is a slow process requiring dedicated, painstaking work (Hansen, 1994).…”
Section: Ecology -The Achilles Heel Of Monitoringmentioning
confidence: 99%